A modernized control system of the “Victoria” pulse modulator complex; Instruments and Experimental Techniques; Vol. 59, № 2 - Pavlov V. M. Vadim Mikhailovich; Baystrukov K. I. Konstantin Ivanovich; Merkulov S. V. Stepan Vadimovich; Golobokov Yu. N. Yury Nikolaevich; Malchukov A. N. Andrey Nikolaevich; Mezentsev A. A. Anton Alekseevich; Lobes L. A. Leonid Anatolievich; Lee A. M. Aleksey Mikhailovich; Iljinykh S. A. Stanislav Alekseevich; Sokolov M. M. Mikhail Mikhaylovich; Nikolaev A. V. Aleksey Vladimirovich; Ovchinnikov A. V. Anton Viktorovich; et al. (2016, 2016)
Title screen